Study on landfill spatial contaminant distribution and potential terrestrial fern species as phytoremediation agent - Nur Hanie binti Mohd Latiff (International Institute for Halal Research and Training, International Islamic University Malaysia, 2019)
As a developing country, Malaysia is facing a problem with waste management issues. Even though landfilling is preferable due to its low cost, availability of land and environmentally friendly method, the problem caused by the dumping sites is not adequately treated. During rainy season, leachate may accelerate heavy metals toxicity at the landfill areas into ground surface. Therefore, this research aimed to study pattern distribution of landfill contaminants as well as to explore the capabilities of fern species as phytoremediation agent. In order to achieve the goal, there are two objectives that need to be fulfilled. Firstly is to study spatial distribution and potential of landfill contaminant at active and closed landfills at different depths (0 cm to 30 cm, 30 cm to 60 cm and 60 cm to 90 cm) and radiuses (5 m to 10 m, 10 m to 15 m, and 15 m to 20 m). Secondly, to assess type of fern species ability and stability as phytoremediation agent. By using hand auger, samples were taken from three (3) different localities in Perak, Selangor and Johor in order to investigate their massive metal sequestration rate stability and pattern distribution in this highly weathered soil. Nine landfill sites located in the state of Selangor comprising of a variety of active and closed landfills chosen. Phytoremediation technology that uses living plant is adopted to accumulate and remove various heavy metals toxicity. This is because phytoremediation activity in plant system functions to degrade, extract or inactivate potentially hazardous compounds in the contaminated soil. Four terrestrial fern species namely; Dicranopteris linearis, Nephrolepis bifurcata, Stenochlaena palustris and Acrostichum aureum were chosen to sequester heavy metal contaminants from laterite soil. Samples that taken from vegetative parts, soils and roots of the plant, were then taken to the laboratory for cleaning and drying purposes before the analysing process. Soils and plants sampling were measured using ICP-MS (Perkin Elmer NexION 300X) for ten heavy metals element (Al, Fe, Cr, Mn, Co, Ni, Cu, Zn, Cd and Pb). Both results showed Al and Fe were detected with the highest concentrations. Al and Fe concentration for landfill soils were detected highest at every radiuses and depths of the landfill sites regardless other heavy metals were detected low due to leach out to the groundwater level. The analysis of variance (ANOVA) output has shown a statistically significant difference (P<0.0001), in the mean of heavy metal concentrations between different radiuses and different depths at all interactions. While the age pattern of landfill shows that the concentration of heavy metals is increasing as the radiuses and depth of soil increase. In order to certify the potential of fern species as a phytoremediation agent to remediate heavy metals toxicity in the landfill soil, the evaluation of bio-concentration factor (BCFs) and translocator factor (TFs) were implemented. The ANOVA output has shown a statistically significant difference (P<0.0001), in the mean of concentrations of heavy metals between vegetative part, root and soil at all interactions. Therefore, it is indicated that all four terrestrial fern species are potential as phytoremediation agents to sequester Cr, Mn, Co, Ni, Cu, Zn, Cd and Pb from landfill sites. Since there are many factors that contributed to the heavy metal accumulation, fern species are suggested to be one of the alternative measures to remediate the soil and remove heavy metals toxicity. In addition to its potential as a green technology, ferns can also be commercialised as an inexpensive alternative method to clean areas that contaminated with heavy metals toxicity.